Sharing information is probably more helpful than providing generic training recommendations on return to play after COVID-19 home confinement - Impellizzeri, F. M.; Franchi, M. V.; Sarto, F.; Meyer, T.; Coutts, A. J. (Science and Medicine in Football, 2020)
Some authors of this editorial have recently published a call for awareness about the health consequences (e.g. increased injury risk) of home confinement in sport programming (Sarto et al. 2020). The main message of that editorial can be summarised as follows: